2020
DOI: 10.32598/hdq.5.4.222.8
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of Factors Influencing Injury and Death by Accident Using Analytical Approach: A Case Study of Ilam Province Roads

Abstract: Background: Every year many people are killed or injured in road accidents. The first step in planning to reduce accidents is to identify the causes of accidents. This study aimed to investigate and identify the causes and factors affecting the incidence and the severity of road accidents as a major issue in Ilam Province, Iran. Materials and Methods: This research is a descriptive study with an analytical approach. Descriptive and inferential statistics indices were used for statistical analysis. A researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Overall, the main causes of road accidents in Iran can be categorized into three groups: Several common causes contribute to all three main factors leading to accidents, including anger and stress, boredom and tiredness, fatigue and sleepiness, lack of driving skills, use of drugs, alcohol, and sleeping pills, and use of mobile phones. These factors are controllable by drivers (Human factors) and align with the findings of previous accident-related research by Vakil al-Roaya & Zargar [ 9 ], Zhang and Proppe [ 12 ], Hammad et al [ 14 ], Jalilian et al [ 15 ], and Omidi, Jafari Skandari & Omidi [ 24 ]. However, unfortunately, most drivers do not pay adequate attention to these factors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, the main causes of road accidents in Iran can be categorized into three groups: Several common causes contribute to all three main factors leading to accidents, including anger and stress, boredom and tiredness, fatigue and sleepiness, lack of driving skills, use of drugs, alcohol, and sleeping pills, and use of mobile phones. These factors are controllable by drivers (Human factors) and align with the findings of previous accident-related research by Vakil al-Roaya & Zargar [ 9 ], Zhang and Proppe [ 12 ], Hammad et al [ 14 ], Jalilian et al [ 15 ], and Omidi, Jafari Skandari & Omidi [ 24 ]. However, unfortunately, most drivers do not pay adequate attention to these factors.…”
Section: Discussionsupporting
confidence: 82%
“…Ashley et al [ 23 ] focused on reduced visibility while driving and identified factors such as fog, smoke, dust, and severe storms as contributors to reduced visibility and accidents leading to fatalities. Omidi et al [ 24 ] investigated the factors influencing injuries and deaths in accidents in Ilam Province, Iran, classifying climate and wind factors as environmental causes and evaluating their impact from the drivers' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers categorized these factors into human error, road environment and vehicle conditions (5,6). Human behavior is the most common contributing factor to RTIs (7,8). Accordingly, there is an urgent need to investigate the impact of human behavior on road safety.…”
Section: Introductionmentioning
confidence: 99%